FUN_COLLOID: An Interactive Multimedia Learning Platform for Understanding Colloids - Rabiah Afifah Daulay; Mutiara Agustina Nasution; Kezia Merry Ivanya Devita Purba; Mella Amilasti Naila; Mutiara Ardi; Nurul Aliyyah; Sarah Agnesia Sinaga; Desy Rahmayanti Hasibuan (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This research aims to develop an engaging and effective learning tool that motivates students to learn more effectively and understand scientific concepts more deeply. This article introduces FUN_COLLOID, an interactive multimedia learning platform designed to enhance students' understanding of colloids, a crucial topic in chemistry. The methods used in this study include the development of interactive multimedia content, such as educational videos, virtual laboratories, and quizzes, as well as the evaluation of their impact on students' interest and understanding. The results showed that the use of FUN_COLLOID significantly improved students' understanding of colloid concepts, as well as increased their involvement in the learning process. The conclusion of this study emphasizes the importance of innovation in learning media to improve the quality of education in Indonesia, and provides recommendations for the further development of this platform so that it can be used in various other learning contexts.